Lotus (Nelumbo nucifera): a multidisciplinary review of its cultural, ecological, and nutraceutical significance - Hang Yang; Simai He; Qi Feng; Zisen Liu; Shibin Xia; Qiaohong Zhou; Zhenbin Wu; Yi Zhang (Bioresources and Bioprocessing)
Abstract This comprehensive review systematically examines the multifarious aspects of Nelumbo nucifera, elucidating its ecological, nutritional, medicinal, and biomimetic significance. Renowned both culturally and scientifically, Nelumbo nucifera manifests remarkable adaptability, characterized by its extensive distribution across varied climatic regions, underpinned by its robust rhizome system and prolific reproductive strategies. Ecologically, this species plays a crucial role in aquatic ecosystems, primarily through biofiltration, thereby enhancing habitat biodiversity. The rhizomes and seeds of Nelumbo nucifera are nutritionally significant, being rich sources of dietary fiber, essential vitamins, and minerals, and have found extensive culinary applications. From a medicinal perspective, diverse constituents of Nelumbo nucifera exhibit therapeutic potential, including anti-inflammatory, antioxidant, and anti-cancer properties. Recent advancements in preservation technology and culinary innovation have further underscored its role in the food industry, highlighting its nutritional versatility. In biomimetics, the unique "lotus effect" is leveraged for the development of self-cleaning materials. Additionally, the transformation of Nelumbo nucifera into biochar is being explored for its potential in sustainable environmental practices. This review emphasizes the critical need for targeted conservation strategies to protect Nelumbo nucifera against the threats posed by climate change and habitat loss, advocating for its sustainable utilization as a species of significant value. Graphical Abstract